High speed solid rotor permanent magnet machines: concept and design - Arumugam, Puvaneswaran; Xu, Zuyuan; La Rocca, A.; Vakil, Gaurang; Dickinson, Matthew; Amankwah, Emmanuel K.; Hamiti, Tahar; Bozhko, Serhiy; Gerada, C.; Pickering, Steve (Institute of Electrical and Electronics Engineers, 2016)
This paper proposes a novel solid rotor topology for an Interior Permanent Magnet (IPM) machine, adopted in this case for an aircraft starter-generator design. The key challenge in the design is to satisfy two operating conditions which are: a high torque at start and a high speed at cruise. Conventional IPM topologies which are highly capable of extended field weakening are found to be limited at high speed due to structural constraints associated with the rotor material. To adopt the IPM concept for high speed operation, it is proposed to adopt a rotor constructed from semi-magnetic stainless steel, which has a higher yield strength than laminated silicon steel. To maintain minimal stress levels and also minimize the resultant eddy current losses due to the lack of laminations, different approaches are considered and studied. Finally, to achieve a better tradeoff between the structural and electromagnetic constraints, a novel slitted approach is implemented on the rotor. The proposed rotor topology is verified using electromagnetic, static structural and dynamic structural Finite Element (FE) analyses. An experiment is performed to confirm the feasibility of the proposed rotor. It is shown that the proposed solid rotor concept for an IPM fulfils the design requirements whilst satisfying the structural, thermal and magnetic limitations.